A escola e a formação de leitores: um olhar na perspectiva da estética da recepção - Cruz, Adriana Santana da (2017)
This research comes out from the concerns of a literary reader who became a Portuguese Language teacher, and who, because of this choice, came to live closely with the contradictions that are revealed within the space that is intended to be privileged in the role of forming readers: school. Mobilized by the objective of understanding how the students receive the literature proposed by the school and the consequent sense that they attribute to the institution in this question, six subjects of basic education were defined as subjects of this study who already had a certain approximation with the literary reading. All the collaborators come from the countryside and are enrolled in Joaquim Inácio de Carvalho State High School, located in the municipality seat of Irará-Ba. In this sense, the corpus of this research privileges the reading trajectory of the subjects, whose roots are embedded in the first eavesdropping, therefore in the oral tradition and the encounter between this trajectory and the school institution. The data collected, first in the focus group session and then in the semi-structured interviews, are analyzed qualitatively in the light of the postulates of the Theory of Reception Aesthetics in dialogue with other theorists and scholars of this topic. It was possible to perceive that the likes these young readers does not dialogue with the school practices, since they transit among the self-help, the best sellers or the fanfics, being opposed to the canonized literature characteristic of the school programs. These data expose, on the one hand, the weaknesses present in the context of the so-called Basic Education that go from the disagreement among oral discursive practices and the literacy process, passing through the curricular discontinuity between the stages, Fundamental and High School, to negligence, when not the negation, of the reading practices of young readers, which could serve as a market entry to texts of greater aesthetic quality. On the other hand, however, these same data point to the fact that it is in the school context favors, even if indirectly, the approximation with the literary reading.